THE ROLE OF THE ENTREPRENEURIAL ECOSYSTEM IN GROWING MOTIVATION AND INTEREST IN ENTREPRENEURSHIP - Bahri Bahri; Fikri Alamsyah (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2024)
The high unemployment rate for college graduates is a big problem in Indonesia. Indonesia's many educated unemployed are due to the need for more interest in entrepreneurship. The entrepreneurial ecosystem can play an essential role in reducing the number of educated unemployed by giving birth to new entrepreneurs. The total sample size is 55 students. Samples were taken using a purposive sampling technique. Data analysis methods include validity tests, reliability tests, t-tests, f-tests, and coefficient of determination tests. The test results reveal that entrepreneurial motivation is directly influenced by entrepreneurial education, family environment, and community environment, but the social environment cannot provide internal motivation. Likewise, interest in entrepreneurship, entrepreneurial motivation, entrepreneurship education, and family environment have a direct influence, while the community environment has no influence. Entrepreneurial motivation failed to act as a connecting variable between entrepreneurship education, family environment, and community environment on students' entrepreneurial interest. The results of tests carried out simultaneously with entrepreneurship education, family environment, and community environment can influence students' entrepreneurial motivation and interest.